Theories of immaterial labour: a critical reflection based on Marx. (1st July 2014) - ,
Abstract : Proponents of the notion of a ''knowledge economy'' argue that immaterial labour is the main productive force in contemporary society. This article takes issue with this view. It critically assesses the concepts of labour, value and class that underlying these arguments and seeks to find alternatives to them. It then goes on to propose an alternative interpretation that, in the author's view, is more closely aligned to the general principles of Marxist theory. It concludes that the ''knowledge economy'' theorists demonstrate an analytical reductionism: by limiting the definition of ''labour'' to physical industrial labour performed in a factory, by reducing the concept of ''value'' to an arithmetically measurable expression of exploitation in the manufacture of goods, and by restricting the concept of ''working class'' or ''proletariat'' to the position of the manual labourer. It concludes that the thesis which presents immaterial labour as a new productive force and announces the end of labour, value and the working class ignores the realities of the processes of labour precarisation currently taking place around the globe.